A new Crossodactylodes Cochran, 1938 (Anura: Leptodactylidae: Paratelmatobiinae) from the highlands of the Atlantic Forests of southern Bahia, Brazil - Teixeira, Mauro Jr.; Recoder, Renato Sousa; Amaro, Renata Cecília; Damasceno, Roberta Pacheco; Cassimiro, José; Rodrigues, Miguel Trefaut (Zootaxa, 2013)
A new Crossodactylodes is described from Serra das Lontras, in the highlands of the Atlantic Forests of southern Bahia. The new species can be distinguished from all other Crossodactylodes by having Finger I ending in an acute tip, a larger body size, by cranial features, and by molecular data. Like their congeners, the new species live in bromeliads but is widely geographically disjunct, being apparently restricted to the summit of a mountain range in Northeastern Brazil.